Motivations for Choosing Field of Study among Medical and Dental Students of Tabriz University of Medical Sciences, Tabriz, Iran - Fahimeh Hamedi Rad; Tahereh Ghaffari; Ehsan Hoshyar (Tabriz University of Medical Sciences, 2014)
Introduction: Our aim was to evaluate factors affecting the choices made by first-year dental and medical students in Tabriz University of Medical Sciences, Iran.Methods: The subjects in the present descriptive cross-sectional study consisted of 104 first-year dental and medical students in the University in 2012‒2013. A questionnaire was given to the students, which included demographic data and prioritization of motives. In designing the questionnaire, nine items were taken into account including income, social status, owning a private office, serving the community, feasibility of working with the hands, self-regulation of working hours, an interest in the field, recommendation by the family and communication, and contact with community members. Data were analyzed with the Mann-Whitney U test using SPSS. Results: Enjoying a high social status was the most important factor (94.2%) in choosing dentistry as a major by dental students. An interest in the field (88.2%) was the second factor in their selection of dentistry. Recommendation by the family and serving the community with a frequency of 50% and contact with community members with a frequency of 51% were the least important in choosing dentistry. A high social status (75%) was the most important factor in choosing medicine as a major by medical students. A high income (73.1%) was the second factor in choosing medicine for them. Serving the community with 43.1% and the feasibility of working with the hands with 28.9% were the least important factors in choosing medicine. Conclusion: Dentistry and medicine are professions that still enjoy a high social status and most students choose these majors in order to attain such status. Differences in motives behind choosing a major by students of these two fields are related to the nature of the professions.